Understanding China’s Role Within the Current International and Regional Orders - Rubiolo, María Florencia (2023)
The debate around the role of China in the current international order continues to be divisive within the theoretical discussions of International Relations. Is Beijing seeking to establish a neworder? Or, considering the current challenges faced by the liberal international order, is it redefining some of its practices and principles while still playing a vital role in sustaining it? The articleargues that, on the global level, China’s international policy has sought to adapt and incorporate itself into the prevailing multilateral structure, but with a selective approach. On a regional level, however, Beijing has developed a set of policies based on fundamental liberal economic practices and mechanisms to boost trade and finance through regional integration and interdependence.To reach these conclusions, this article takes a qualitative methodological approach using an in-depth review of secondary sources to frame the central theoretical discussion, accompaniedby analysis of primary statistical data. The specific cases analyzed are the BRI in East Asia and RCEP, both structures of regional governance.